Comparison on students’ motivation in learning music between China and Hong Kong / Debbie Mitchelle Robben - Mitchelle Robben, Debbie (Faculty of Music, 2013)
The purpose of this study was to explore whether there are comparisons between two countries, namely China and Hong Kong, on students and parents' perception towards learning music and the factors that affect students' motivation in learning music. Secondary data was used where articles, journals, books, and previous related researches became the source of information for this study. Findings suggest that students and parents' perception towards learning music between these two countries is more or less the same and the factors that affect students' motivation in learning music are generally the same and show not much of a difference.